Study protocol: Cerebral autoregulation, brain perfusion, and neurocognitive outcomes after traumatic brain injury -CAPCOG-TBI - Caldas, Juliana; Cardim, Danilo; Edmundson, Philip; Morales, Jill; Feng, Aaron; Ashley, John Devin; Park, Caroline; Valadka, Alex; Foreman, Michael; Cullum, Munro; Sharma, Kartavya; Liu, Yulun; et al. (Frontiers in Neurology, 2024)
Background: Moderate-severe traumatic brain injury (msTBI) stands as a prominent etiology of adult disability, with increased risk for cognitive impairment and dementia. Although some recovery often occurs within the first year post-injury, predicting long-term cognitive outcomes remains challenging, partly due to the significant pathophysiological heterogeneity of TBI, including acute cerebrovascular injury. The primary aim of our recently funded study, cerebral autoregulation, brain perfusion, and neurocognitive outcomes after traumatic brain injury (CAPCOG-TBI), is to determine if acute cerebrovascular dysfunction after msTBI measured using multimodal non-invasive neuromonitoring is associated with cognitive outcome at 1-year post-injury.Methods: This longitudinal observational study will be conducted at two Level 1 trauma centers in Texas, USA, and will include adult patients with msTBI, and/or mild TBI with neuroimaging abnormalities. Multimodal cerebral vascular assessment using transcranial Doppler and cerebral near-infrared spectroscopy (NIRS) will be conducted within 7-days of onset of TBI. Longitudinal outcomes, including cognitive/functional assessments (Glasgow Outcome Scale and Patient-Reported Outcomes Measurement Information System), cerebral vascular assessment, and imaging will be performed at follow-ups 3-, 6-, and 12-months post-injury. We aim to recruit 100 subjects with msTBI along with 30 orthopedic trauma controls (OTC). This study is funded by National Institute of Neurological Disease and Stroke (NINDS) and is registered on Clinicaltrial.org (NCT06480838).Expected results: We anticipate that msTBI patients will exhibit impaired cerebrovascular function in the acute phase compared to the OTC group. The severity of cerebrovascular dysfunction during this stage is expected to inversely correlate with cognitive and functional outcomes at 1-year post-injury. Additionally, recovery from cerebrovascular dysfunction is expected to be linked to cognitive recovery.The results of this study could help to understand the contribution of cerebrovascular dysfunction to cognitive outcomes after TBI and pave the way for innovative vascular-focused interventions aimed at enhancing cognitive recovery and mitigating neurodegeneration following msTB. In addition, its focus towards personalized medicine to aid in the management and prognosis of TBI patients.